Comparative Study of Rigid Pavement Design of Solo-Yogyakarta-NYIA Kulon Progo Toll Road Using MDPJ 2017 and MDPJ 2024 - Tolab, Laziqoh Zahatul; Fauziah, Miftahul (ASTONJADRO, 2025)
The Solo-Yogyakarta-NYIA Kulon Progo Toll Road is one of Proyek Strategis Nasional (PSN) that has an important role in the smooth movement of traffic. The infrastructure development process must be carefully considered, especially at the planning stage. This paper analyzes the design of rigid pavement planning using MDPJ 2017 and MDPJ 2024 to determine the difference in design results and can be the best alternative design proposal so that it can provide a reference for pavement performance performance. In addition, an empirical mechanistic analysis was conducted using KENSLAB in the KENPAVE program. The program outputs stress, deflection, and service life prediction. The analysis results show that MDPJ 2017 and MPDJ 2024 with JSKN value of 125,538,693,248 have the same rigid pavement thickness value of 305 mm and with KENSLAB analysis, a service life of 1000 years is obtained. MDPJ 2017 and MPDJ 2024 do not produce significant differences, there are only differences in the tie bar spacing and dowel diameter. The different tie bar spacing and dowel diameters have little effect on the value difference in the KENPAVE output. However, the design with MDPJ 2024 has a slightly higher value than MDPJ 2017. Thus, alternative designs are needed to make the pavement performance more effective and efficient, including 200 mm, 185 mm, and 180 mm thick. From several alternative pavement designs, it is concluded that the design that produces the most optimal performance is alternative 3 with a layer arrangement of 180 mm thick slab, 100 mm LMC, and 150 mm LPA with a predicted service life of 48.2 years.